2009
DOI: 10.1111/j.1742-4658.2009.07211.x
|View full text |Cite
|
Sign up to set email alerts
|

The βN‐acetylglucosaminidases NAG1 and NAG2 are essential for growth of Trichoderma atroviride on chitin

Abstract: The chitinolytic enzyme machinery of fungi consists of chitinases and β‐N‐acetylglucosaminidases. These enzymes are important during the fungal life cycle for degradation of exogenous chitin, which is the second most abundant biopolymer, as well as fungal cell‐wall remodelling. In addition, involvement of chitinolytic enzymes in the lysis of the host cell wall in mycoparasitic Trichoderma spp. has been reported. In view of the fact that fungi have on average 15–20 chitinases, but only two β‐N‐acetylglucosamini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The dispensable role of N- acetyl-ß-D-glucosaminidase to biocontrol activity was proposed previously [16] and our work supports this suggestion. Our findings are also consistent with a recent study by [59] that showed that the biocontrol efficacy of T. atroviride was unaffected by single and double deletions of the nag1 and nag2 genes.…”
Section: Discussionsupporting
confidence: 93%
“…The dispensable role of N- acetyl-ß-D-glucosaminidase to biocontrol activity was proposed previously [16] and our work supports this suggestion. Our findings are also consistent with a recent study by [59] that showed that the biocontrol efficacy of T. atroviride was unaffected by single and double deletions of the nag1 and nag2 genes.…”
Section: Discussionsupporting
confidence: 93%
“…Growth on chitin was tested in static liquid cultivations with SM medium, 1% chitin, and 0.1% peptone (27) and on the same medium in agar plates solidified with 1.5% agar with and without peptone. Biomass measurements from liquid cultivations and assessment of sporulation rates on agar plates were carried out as described (31). Furthermore, hydrophobicity of the mycelium was assessed by pipetting water droplets on the mycelium as has been described previously for Trichoderma reesei hydrophobin knock-out strains (32).…”
Section: Methodsmentioning
confidence: 99%
“…Since expression of the chitinase genes, chi42 [17] and nag1 [18], have been demonstrated to contribute to disease suppression in Trichoderma, their expression during reduction in FA level was analyzed using the RNA samples. While ech42 expression was slightly repressed at 400 ppm of FA, nag1 was significantly repressed at 300 ppm.…”
Section: Discussionmentioning
confidence: 99%